2009
DOI: 10.1111/j.1468-2982.2008.01698.x
|View full text |Cite
|
Sign up to set email alerts
|

Parental Psychopathology and Migraine Headaches among Adolescent Girls

Abstract: Migraine headaches and depression often co-occur within individuals, and both syndromes run in families. However, knowledge about how these disorders relate across generations, as well as how migraine relates to other forms of psychopathology, is sparse. This study examined risk for migraine among female adolescent offspring of parents with different types of psychopathology. The sample was drawn from the Minnesota Twin Family Study, a community-based study of adolescents and their families (n = 674, 17-year-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
0
8
0
1
Order By: Relevance
“…This means that the mothers of patients with headaches did not show higher levels of alexithymia compared to other mothers. Differences, if any exist, between mothers of TTH and M patients and mothers of the control group, might lie in other aspects of emotional regulation implied in mood and anxiety disorders, which have an high incidence in parents of children with headache [ 17 , 40 , 41 ]. Future studies exploring these aspects may be useful to tackle important stressors and risk factors for the onset of headaches in genetically predisposed children [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This means that the mothers of patients with headaches did not show higher levels of alexithymia compared to other mothers. Differences, if any exist, between mothers of TTH and M patients and mothers of the control group, might lie in other aspects of emotional regulation implied in mood and anxiety disorders, which have an high incidence in parents of children with headache [ 17 , 40 , 41 ]. Future studies exploring these aspects may be useful to tackle important stressors and risk factors for the onset of headaches in genetically predisposed children [ 16 , 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Future studies should include fathers to further explore the mechanisms involved in family emotional functioning and in the intergenerational transmission of alexithymia [ 38 ]. Close family members need to be involved in the assessment of psychological traits and emotional competencies that may constitute a risk or, on the contrary, a protective factor for the onset of the child’s headache [ 16 , 17 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, studies have demonstrated an association between parental psychopathology and offspring headaches including migraine (Feldman et al, 2010; Marmorstein et al, 2009). However, to our knowledge, no previous study has examined the association between BD and comorbid migraine, adjusting for parental psychopathology.…”
Section: Introductionmentioning
confidence: 95%
“…10 Ebeveynlerinde psikopatoloji olan kız ergenlerin araştırıldığı bir çalışmada ise migren sıklığının daha fazla olduğu görülmüştür. 52 Çalışmamızda annelerde bulunan yüksek depresyon düzeyleri, baş ağrısı olan çocukların değerlendirilmesinde ebeveyn değerlendirilmesinin önemli olabileceğini göstermektedir. Araştırmalar çocuklardaki kronik ağrısı ile annelerin psikolojik durumu ve stres düzeyi ile iki yönlü bir ilişkisi olduğunu söylemektedir.…”
Section: Discussionunclassified